A Study of the Provisions for Dispute Resolution in the Health Sector through Mediation and Arbitration in Indonesia - Jafar Sidik; Dewi Sulistianingsih; Asep Rozali; Deni Haspada; Edi Pramono (The Indonesian Journal of International Clinical Legal Education, 2024)
One of the ideals of the Indonesia nation is to advance general welfare. Health is a human right as one of the elements of general welfare, which must be realized. Legal relations in the health sector are not always harmonious, therefore it is necessary to have a way or mechanism to resolve disputes or disputes or differences of opinion between related parties, such as the relationship between health facilities in the form of hospitals or clinics and doctors, doctors, or other related parties. The political direction of Indonesia's law regarding dispute resolution can be carried out through state judicial institutions or resolved outside the state courts. The purpose and purpose of this article is to know, describe and analyze positive legal provisions related to dispute resolution in the health sector. This study uses research methods with juridical-normative and descriptive-analytical approaches, using library research. The results of this study show that the provisions in the Health Law have accommodated efforts to resolve disputes outside the court by using arbitration and mediation. However, there is still a need for health mediation institutions at the district level so that there are institutions available to resolve disputes in the health sector.